2017
DOI: 10.4018/ijpada.2017070105
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Facebook by the Arab World Governments

Abstract: This study explored the importance of social media as a communication channel, and the reasons that lead governments to adopt such channel in their communication. Twelve Arab governments out of all twenty-two Arab countries adopted such strategy and were included in the authors' sample. Governments who adopted such a channel successfully communicated with citizens utilizing commonly used post properties (i.e. Likes, Comments and Shares). This study found that Arab governments posted news and information on Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Social media has enabled multiple features including communication and participating opportunities and allowing direct instant interactions between parties (Dennen and Bruner, 2014). Social media offers many services and benefits like encouraging citizens to sharing their opinions and information, enhancing the relationship between G2C and increasing the collaboration and communication between both parties (Mishaal and Abu-Shanab, 2017). The major features that SNs offer is the ease of access and reach to any person on the internet, which made governments join such platforms to improve the relationship with citizens (Khasawneh and Abu-Shanab, 2013).…”
Section: An Overview Of Sns: Facebookmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media has enabled multiple features including communication and participating opportunities and allowing direct instant interactions between parties (Dennen and Bruner, 2014). Social media offers many services and benefits like encouraging citizens to sharing their opinions and information, enhancing the relationship between G2C and increasing the collaboration and communication between both parties (Mishaal and Abu-Shanab, 2017). The major features that SNs offer is the ease of access and reach to any person on the internet, which made governments join such platforms to improve the relationship with citizens (Khasawneh and Abu-Shanab, 2013).…”
Section: An Overview Of Sns: Facebookmentioning
confidence: 99%
“…Only 12 countries out of the 22 Arab countries included in the study communicated with citizens utilising Facebook features. The authors utilised citizens records related to their likes, comments and shares (Mishaal and Abu-Shanab, 2017). The results of the study indicated that posting over Facebook was very poor and using multimedia encouraged more communication between involved parties.…”
Section: Facebook and E-governmentmentioning
confidence: 99%
“…Other studies in the MENA country of Oman found that government agencies failed to take full advantage of SNS to design and deliver more collaborative, participatory, and interactive relationships with citizens (Al‐Aufi et al, 2017; Dalwai et al, 2020). A recent study found that most Arab governments used Facebook for self‐promotion and information dissemination rather than being genuinely open with their citizenry (Mishaal & Abu‐Shanab, 2017). A similar finding was reached by a previous study that found that most Arabic governments were doing very little to encourage online participation (Halpern et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%